Perianastomotic ulceration presenting with long-term iron deficiency anemia and growth failure: A case report and review of the literature - Kyung Ji Kang; Eun Ha Kim; Eun Young Jung; Woo-Hyun Park; Yu-Na Kang; Ae Suk Kim; Jin-Bok Hwang (Korean Pediatric Society, 2010)
Perianastomotic ulceration (PAU) rarely occurs after small bowel resection in infancy. Since the understanding of its pathogenesis is incomplete, an effective method of treatment has not yet been discovered. We report the first case in Korea of a 10-year-old girl with chronic iron deficiency anemia (IDA) and growth failure who was diagnosed with PAU at colonoscopy. Seven years were required to identify the cause of IDA. After surgical resection and revision of anastomosis, a close follow-up is being conducted due to the risk of recurrence. Here, we also review reports on 25 pediatric patients with PAU derived from a search of the English-language literature and describe the clinical features of PAU along with the results of treatment.